The retail diversity index: A tool to characterize consumer’s food environment in LMICs - Hernandez, Ricardo; Bene, Christophe; Nguyen, Manh Cuong; Talsma, Elise; Even, Brice; Thai, Hang T M (2024)
The purpose of this study is to characterize the food diversity available to consumers from all types of food retailers and food outlets within a given area through the use of a Retail Diversity Index (RDI). Dietary diversity is an important component of healthy diets, whether consumers eat healthy is based on their food choices which are influenced by numerous factors such as the diversity and the affordability of healthy foods.